Plant reproduction is altered by simulated herbicide drift to constructed plant communities. (5th June 2017) - Olszyk, David; Pfleeger, Thomas; Shiroyama, Tamotsu; Blakeley‐Smith, Matthew; Lee, E. Henry; Plocher, Milton
Abstract: Herbicide drift may have unintended impacts on native vegetation, adversely affecting individual species and plant communities. To determine the potential ecological effects of herbicide drift, small plant community plots were constructed using 9 perennial species found in different Willamette Valley (OR, USA) grassland habitats. Studies were conducted at 2 Oregon State University (Corvallis, OR, USA) farms in 2 separate years, with single and combined treatments of 0.01 to 0.2× field application rates (f.a.r.) of 1119 g ha −1 for glyphosate (active ingredient [a.i.] of 830 g ha −1 acid glyphosate) and 560 g ha −1 a.i. for dicamba. Plant responses were percentage of cover, number of reproductive structures, mature and immature seed production, and vegetative biomass. Herbicide effects differed with species, year, and, to a lesser extent, farm. Generally, 0.1 to 0.2× f.a.r. of the herbicides were required to affect reproduction in Camassia leichtlinii, Elymus glaucus, Eriophyllum lanatum, Festuca idahoensis, Iris tenax, and Prunella vulgaris . Eriophyllum lanatum also had a significant increase in percentage of immature seed dry weight with 0.01× f.a.r. of dicamba or the combination of glyphosate plus dicamba. Other species showed similar trends, but fewer significant responses. These studies indicated potential effects of low levels of herbicides on reproduction of native plants, and demonstrated a protocol whereby species growing in a constructed plant community can be evaluated for ecological responses. Environ Toxicol Chem 2017;36:2799–2813. Published 2017 SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.